2020
DOI: 10.1038/s41598-020-78284-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and validation of diffusion MRI-based fiber tracking with neural tracer data as a reference

Abstract: Diffusion-weighted magnetic resonance imaging (dMRI) allows non-invasive investigation of whole-brain connectivity, which can reveal the brain’s global network architecture and also abnormalities involved in neurological and mental disorders. However, the reliability of connection inferences from dMRI-based fiber tracking is still debated, due to low sensitivity, dominance of false positives, and inaccurate and incomplete reconstruction of long-range connections. Furthermore, parameters of tracking algorithms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…AI can also help in the research of functional brain mapping. Researchers from Japan Gutierrez et al, [112] used machine intelligence based on CNN to accelerate and improve the correctness of an effective brain connection mapping technique. AI can assist in the branch of neuro-oncology for assessment and diagnosis of brain tumors.…”
Section: ) Neurologymentioning
confidence: 99%
“…AI can also help in the research of functional brain mapping. Researchers from Japan Gutierrez et al, [112] used machine intelligence based on CNN to accelerate and improve the correctness of an effective brain connection mapping technique. AI can assist in the branch of neuro-oncology for assessment and diagnosis of brain tumors.…”
Section: ) Neurologymentioning
confidence: 99%
“…Compared with prior human CRP tractography studies, this work features several methodologic advances to improve accuracy & reliability, including: greater sample size, upgraded MRI hardware, [51,94] higher spatial & angular resolution, [51,74,94] better distortion correction, [51,53,74] advanced model-free reconstruction of diffusion orientations (for improved resolution of multiple fiber populations within a voxel and partial volume effects), [30,55,72,[95][96][97] group-averaging of diffusion orientations prior to tractography, [30,54] and more anatomically-informed delineation of tractography regions [2,7,[27][28][29]48,50,74] (Table 1).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…MRI-based diffusion tractography is a non-invasive method that estimates tract trajectories by simulating streamlines through pre-processed diffusion-weighted images. [27][28][29][30] One research group has begun mapping the healthy human CRP using this method (Table 1). [31][32][33][34] Primarily focusing on CRP origins in the secondary motor cortices (supplementary motor area & premotor cortex), studies from this group have reported a CRP trajectory through the superior corona radiata, posterior limb of the internal capsule (anteromedial to the CST) and midbrain tegmentum (posterior to the CST) to the area of the pontomedullary reticular formation.…”
Section: Introductionmentioning
confidence: 99%
“…While this method provides useful non-invasive, in vivo measures, it is limited by insufficient resolution to resolve axonal bundles and inability to determine the direction of neural conduction (Calamante, 2019). Consequently, it is crucial for diffusion tractography to be guided by anatomical knowledge in order to maximize tract coverage and minimize inclusion of false pathways (Aydogan et al, 2018;Azadbakht et al, 2015;Gutierrez et al, 2020). Unfortunately, this anatomical knowledge is incomplete for the CRP, which limits confidence in prior human CRP mapping (e.g., Jang & Seo, 2014Yeo et al, 2012Yeo et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%